A Candidate Proxy to Be Used in Intensity-Based Triggering Mechanism for Parametric CAT-Bond Insurance: Istanbul Case Study. Issue 2 (May 2019) - Mousavi, Mehdi; Akkar, Sinan; Erdik, Mustafa
We study the suitability of average peak ground acceleration ( PGA ) as a ground-motion proxy for parametric catastrophe bond (CAT bond) design. We tie the selection of PGA (as a triggering parameter for CAT bonds) to computational convenience (fast retrieval from the recorded ground motion) and loss correlation (optimum monetary return on the investor side). Our case studies advocate that PGA, as a candidate ground-motion proxy, can be used confidently for parametric CAT bonds, particularly applications associated with dense coverage of seismic networks. It is still a compelling ground-motion proxy even if the seismic network coverage is sparse, provided that the accelerometric stations are deployed in the vicinity of assets that financially represent the most significant portion of the insured building stock. We establish an event-based risk model of the Istanbul city (via Monte Carlo simulations) to depict the rationale behind our proposition and compare its performance with other competing (more sophisticated) proxies in terms of accelerometric network density and spatial distribution as well as the different risk levels used in risk management.